Native Classical: Musical Modernities, Indigenous Research Methodologies and a Kanienkéha (Mohawk) Concept of Non:wa (Now) - Witzleben, John Lawrence (Université du Maryland, 2014)
In this dissertation I explore how Indigenous methodologies that foreground cultural advocacy, revitalization, and education can be articulated using Indigenous language and cultural metaphor in research on North American Indian composers. Toward this end, I apply the Kanienkéha (Mohawk) concept of "non:wa" or "now" that also refers to three modes of perception--the now of the past, the present, and the future--toward understanding the intersection of innovation and tradition in classical Native music. This research joins the existing discourse that critiques binary oppositions separating Indigenous tradition (as past) and innovation (as present and future). Through interviews, fieldwork, and musical analysis, I illustrate Native values of interconnectedness, relationality, continuity, politics, and soundscapes in the processes of Native composition as well as the resultant works, I explore how these, in turn, may be understood through the application of Indigenous research techniques. In collaboration with a cohort of contemporary musicians, I look primarily at two Navajo composers--Raven Chacon and Juantio Becenti--and examine my own work as a composer, performer, and ethnomusicologist of Kanienkéha descent to explore the following questions: How can the topic of classical Native music best be served by using Indigenous methodologies in fieldwork, research, and representation and What is classical Native Music and is it different from other contemporary classical music styles? Drawing on the teachings of Indigenous dotahs (elders/teachers), the scholarship of ethnomusicologists, and examining oral and written tradition while using language and cosmology as cultural metaphors, I present a variety of possibilities for looking at Indigenous music through Indigenous eyes. Rather than offering a set of conclusions, I offer a set of tools for discussion and reflection: 1) how we might understand a definition of classical Native music; 2) how we are part